La regularización tributaria en el derecho penal peruano: fundamentos, presupuestos y aplicación - Pariona Arana, Raúl (2025)
The article examines tax regularization in the Peruvian legal system, focusing particularly on the foundations that legitimize it, the requirements for its application, and the challenges faced in its practical implementation. The significance of this legal institution lies in its capacity to exempt the perpetrator of a tax crime from criminal prosecution, provided they inform the authority of their unlawful act and pay the full amount of the tax debt generated by the offense, plus interest and the fine. The criminal policy considerations that justify waiving criminal prosecution prioritize the effectiveness of tax collection and acknowledge the achievement of criminal law objectives through this mechanism. The article is structured in five sections comprising: i) an approach to the institution of tax regularization, ii) the foundations of legitimation, iii) the discussion of its legal nature, iv) its requirements, and v) the challenges of practical application in Peru.